On the time transformation of mixed integer optimal control problems using a consistent fixed integer control function - Ringkamp, Maik; Ober-Blöbaum, Sina; Leyendecker, Sigrid (Mathematical Programming, 2016)
Nonlinear control systems with instantly changing dynamical behavior can be modeled by introducing an additional control function that is integer valued in contrast to a control function that is allowed to have continuous values. The discretization of a mixed integer optimal control problem (MIOCP) leads to a non differentiable optimization problem and the non differentiability is caused by the integer values. The paper is about a time transformation method that is used to transform a MIOCP with integer dependent constraints into an ordinary optimal control problem. Differentiability is achieved by replacing a variable integer control function with a fixed integer control function and a variable time allows to change the sequence of active integer values. In contrast to other contributions, so called control consistent fixed integer control functions are taken into account here. It is shown that these control consistent fixed integer control functions allow a better accuracy in the resulting trajectories, in particular in the computed switching times. The method is verified on analytical and numerical example
Keywords: Time transformation Control consistency Optimal control Mixed integer optimal control Hybrid systems Switched dynamical systems